Spectroscopic Studies on the Interaction of Hemin with Human Telomeric G-Quadruplex DNA - Luo, Xu-Jian; Qin, Qi-Pin; Huang, Ke-Bin; Liu, Yan-Cheng; Liang, Hong (Asian Journal of Chemistry, 2013)
The interaction behaviours of hemin as a ligand binding with three types of human telomeric G-quadruplex DNA were examined by UV-visible and circular dichroism spectroscopic methods. The circular dichroism spectra of these three types of G-quadruplex DNA all showed major positive absorption peaks at ca. 290 nm with shoulder peaks at ca. 270 nm, along with a negative absorption peak at ca. 250 nm. The presence of hemin did not induce obvious circular dichroism spectral changes of these G-quadruplex DNA, which indicates that hemin is able to stabilize human telomeric antiparallel G-quadruplex DNA structure. For comparison, the addition of hemin induced obvious increment on the characteristic antiparallel circular dichroism absorption of the corresponding single-chain human telomeric sequences, which suggests that hemin may induce and stabilize the formation of antiparallel G-quadruplex DNA even in the absence of K+. On the other hand, the addition of the three types of G-quadruplex DNA into the hemin solution with gradually increasing concentrations induced significant hypochromicity (31.86-47.26 %) along with 11-23 nm of bathochromicity on the UV-visible absorption of hemin. From this result, it is suggested that the high binding affinity of hemin to antiparallel G-quadruplex DNA is based on the intensive intercalative binding mode of hemin to antiparallel G-quadruplex DNA by the p-p stacking between the macrocyclic aromatic hemin and the guanine quartet.